Relatioship between intestinal microbiotes and depression (Research, Society and Development, 2020)
The research describes the depression disorder and its relationship with the human intestinal microbiota, which leads the individual to be in dysbiosis and its association with the pathology. In this context, it was possible to emphasize the importance of nutritional treatment for these cases. As a methodology, a bibliographic, qualitative and descriptive research was carried out. The search for scientific information available in the literature took place in the electronic databases Scielo, Google Acadêmico and PubMed. Articles were investigated that address mental illnesses with the human microbiota, taking into account what is so eminent in intestinal modulation and which can cause psychic diseases such as depression, and, consequently, the damage that antidepressant treatments bring for our intestinal modulation, published between 1997 and 2019, in Portuguese and English.  The diagnosis of depression comes from many variables, but through this research it is possible to identify a number of reasons for such pathology, such as dysbiosis caused by poor intestinal nutrition, use of drugs to treat the same pathology and an inadequate gastrointestinal tract permeability. Nutrition has a fundamental role in cases, both for the prevention of pathologies and psychological disorders such as depression, and also for the help in its treatment with a specialist such as psychologists and psychiatrics, even though they know the importance of nutrition in the treatment and prevention of depression, yet very little is said about this type of aid, changing habits like eating.